From Emphatic Affirmation to Concessivity: Two Case Studies in the History of Portuguese (Revista de Estudos da Linguagem, 2024)
This paper investigates the diachronic establishment process of two concessive conjunctional periphrases in Portuguese, bem que and se bem que. With theoretical support from Grammaticalization, in particular Traugott and Dasher (2002), Heine and Kuteva (2007), Bybee (2010), and some assumptions from pragmatic theories about concessivity, according to Anscombre (1980), Ducrot (1984), Moeschler and Spengler (1982), Rossari (2014), the main issue is about understanding the link between the semantics of the adverbial source, the contextually induced inferential processes and the type of concessive meaning. The analyses are based on a diachronic sample featuring texts from ancient to modern Portuguese, and on a methodology guided by the the constructions’ polysemic standards with their corresponding distributional properties. The results provide evidence that, despite being two change phenomena which arise in different states of language and distinct contexts, both have the adverb bem at their source, in the role of emphatic affirmation, and both specialize in expressing restrictive concessive relations. The data doubly compatible with source and target interpretations evidences gradual processes from pragmatic towards semantics, in which the concepts of polyphony and argumentative hierarchy are of importance.